Free Will, Black Swans and Addiction - Fenton, Ted (Neuroethics, 2016)
The current dominant perspective on addiction as a brain disease has been challenged recently by Marc Lewis, who argued that the brain-changes related to addiction are similar to everyday changes of the brain. From this alternative perspective, addictions are bad habits that can be broken, provided that people are motivated to change. In that case, autonomous choice or “free will” can overcome bad influences from genes and or environments and brain-changes related to addiction. Even though we concur with Lewis that there are issues with the brain disease perspective, we also argue that pointing to black swans can be important, that is: there can be severe cases where addiction indeed tips over into the category of brain disease, but obviously that does not prove that every case of addiction falls into the disease category, that all swans are black. We argue that, for example, people suffering from Korsakoff’s syndrome, can be described as having a brain disease, often caused by alcohol addiction. Moreover, the brain changes occurring with addiction are related to choice-behaviour (and the related notions of willed action), habit formation and insight, hence essential mental abilities to break the addiction. We argue for a more graded perspective, where both black swans (severe brain disease which makes recovery virtually impossible) and white swans (unaffected brain) are rare, and most cases of addiction come as geese in different shades of gray.